Eksplorasi Implementasi LMS di Perguruan Tinggi: Studi Kualitatif Pengalaman Mahasiswa Indonesia - Anggeraini, Nining (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to uncover the experiences of Indonesian students in utilizing Learning Management Systems (LMS) during their studies in higher education. Through a qualitative approach, it was found that the majority of respondents did not have prior experience using LMS at previous educational levels, making the adaptation process an initial challenge. This research employs a qualitative approach. Using purposive sampling techniques, ten respondents who have used digital technology in their academic activities were selected. Semi-structured interviews were used as the main data collection method. The research results show that LMS plays an important role in supporting academic activities, especially because it provides structured access to lecture materials, learning resources, schedules, and announcements. Flexible features and ease of access also encourage the emergence of self-directed learning initiatives. However, some technical hurdles still exist, such as a less intuitive interface design and inconsistent material presentation across courses. These findings underscore the need for further development of LMS, both from a technical side and usage guidelines, as well as the necessity for instruments to identify the active roles of respondents in using LMS to improve learning outcomes. This study contributes to understanding the dynamics of LMS utilization by respondents, particularly in the context of the transition to digital learning in higher education.